2018
DOI: 10.1096/fj.201800265rr
|View full text |Cite|
|
Sign up to set email alerts
|

Proproliferative function of adaptor protein GRB10 in prostate carcinoma

Abstract: Growth factor receptor‐binding protein 10 (GRB10) is a well‐known adaptor protein and a recently identified substrate of the mammalian target of rapamycin (mTOR). Depletion of GRB10 increases insulin sensitivity and overexpression suppresses PI3K/Akt signaling. Because the major reason for the limited efficacy of PI3K/Akt‐targeted therapies in prostate cancer (PCa) is loss of mTOR‐regulated feedback suppression, it is therefore important to assess the functional importance and regulation of GRB10 under these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…GRB10 knockdown in AR‐positive LNCaP and C4‐2 PCa cells inhibited cell proliferation, while its overexpression promoted ENZ resistance. Our findings were later independently confirmed in vivo by another research group 9 . However, the precise mechanism mediated by GRB10 in CRPC development remains unclear.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…GRB10 knockdown in AR‐positive LNCaP and C4‐2 PCa cells inhibited cell proliferation, while its overexpression promoted ENZ resistance. Our findings were later independently confirmed in vivo by another research group 9 . However, the precise mechanism mediated by GRB10 in CRPC development remains unclear.…”
Section: Introductionsupporting
confidence: 66%
“…GRB10 is reportedly a substrate of mTORC1, where mTORC1 phosphorylates and stabilizes GRB10 in TSC2 ‐deficient models 39 . On the other hand, in PCa models, treatment with either mTOR inhibitors (rapamycin, Torin‐1 and PP242) or amino acid deprivation failed to reduce GRB10 protein expression 9 . In our previous study, we found that the expression of GRB10 mRNA is significantly higher in PTEN ‐deleted clinical PCa 8 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Hundreds of the target genes of miR-222 were predicted using the TargetScan online software, and the GRB10 aroused our attention as it is involved in the regulation of gene transcription and translation, the cell cycle, and cell growth and proliferation by inducing the PI3K-AKT signaling pathway ( Kazi and Ronnstrand, 2013 ; Khan et al, 2019 ; Zhang T. et al, 2019 ). Furthermore, it has been reported that LY294002-induced inhibition of the PI3K/AKT signaling pathway inhibits porcine Sertoli cell proliferation and promotes cell apoptosis ( Gao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%